Comparing Mesoamerica and the Andes through Ethnography: Towards the Construction of a Model for Fieldwork - Lorente Fernández, David (Revista Española de Antropología Americana, 2014)
The aim of this article is not to present a finished model but to suggest different approaches for carrying out comparative ethnographic investigations between Mesoamerica and the Andean regions. It begins with theories that some Mesoamericanistas and Andeanists have developed based on their use of historical sources and adds what can be learned from ethnographic field investigations to make empirical comparisons between both regions. This article explores the validity of using native concepts which can be useful analytical categories to make such comparisons.
Keywords: Cultural comparisons; methodology; ethnography; Mesoamerica; Andes; ritual; cosmology